Confinement and passivation of perovskite quantum dots in porous natural palygorskite toward an efficient and ultrastable light-harvesting system in water. Issue 47 (22nd November 2022) - Meng, Genping; Mu, Xijiao; Zhen, Liping; Hai, Jun; Zhang, Zefan; Hao, Tianzhi; Lu, Siyu; Wang, Aiqin; Wang, Baodui
Abstract : A water-resistant light-harvesting antenna was prepared via encapsulating and in situ passivating perovskite quantum dots in PAL matrix. The ESY-RB-CsPbBr3 @PAL system with high sequential FRET exhibited enhanced photocatalysis in aqueous solution. Abstract : Perovskite quantum dots (QDs) are promising as representative candidates to construct next-generation superior artificial light-harvesting systems (ALHSs). However, their high sensitivity to external environments, especially to water, imposes a stringent limitation for their actual implementation. Herein, by interface engineering and encapsulation with natural palygorskite (PAL), a water-resistant light-harvesting CsPbBr3 @PAL antenna was prepared. Molecular dynamics simulations further confirm a significant shielding protection of the PAL matrix to CsPbBr3, facilitating exceptional stability of the CsPbBr3 @PAL antenna when exposed to air for 10 months, to 150 °C thermal stress, and even to water for more than 30 days, respectively. Furthermore, as a result of in situ encapsulation of the PAL matrix and defect passivation caused by H-bonding and coordination-bonding interaction, the CsPbBr3 @PAL antenna in water shows a substantially enhanced photoluminescence quantum yield (36.2%) and longer lifetime. After sequentially assembling Eosin Y and Rose Bengal in the pores of the PAL matrix, RB-ESY-CsPbBr3 @PAL with a sequential two-step efficient Förster resonance energy transfer process exhibited extremely enhanced photocatalytic activity toward Friedel–Crafts alkylation reactions in aqueous solution, 2.5-fold higher than that of corresponding ESY/RB. Our work provides a feasible strategy for the exploitation of ultra-stable halide perovskite-based ALHSs in aqueous media for solar-energy conversion.